Antiglioma pseurotin A from marine Bacillus sp. FS8D regulating tumour metabolic enzymes. Issue 11 (3rd June 2018) - Anjum, Komal; Bi, Hongyun; Chai, Weiyun; Lian, Xiao-Yuan; Zhang, Zhizhen
Abstract: Pseurotin A was isolated from a culture of marine Bacillus sp. FS8D and showed to be active against the proliferation of four different glioma cells with IC50 values of 0.51–29.3 μM. It has been found that pseurotin A downregulated the expression of tumour glycolytic enzymes pyruvate kinase M2 (PKM2) and lactate dehydrogenase 5 (LDH5) and upregulated the expression of pyruvate dehydrogenase beta (PDHB), adenosine triphosphate synthase beta (ATPB) and cytochrome C (Cyto-C), the important regulators for tricarboxylic acid cycle and oxidative phosphorylation. The data suggested that targeting multiple metabolic enzymes might be one of the antiglioma mechanisms of pseurotin A. Abstract :